The effect of using polypropylene fibers on the durability and fire resistance of concrete - Hassan Suiffi; Anas El Maliki; Fatima Majid; Omar Cherkaoui (Fracture and Structural Integrity)
In order to study the effect of polypropylene fibers on the durability of cementitious composites, several experimental tests have been carried out in the laboratory. The composite was tested with different volume fractions of polypropylene fibers (0.05%, 0.10%, 0.30% and 0.50%). All the results relating to the indicators (porosity accessible to water eb, to the oxygen permeability Kapp.gas and diffusivity Dns) indicate that the addition of polypropylene fibers in a cement matrix represents only a small effect on durability. This panel of general sustainability indicators can be supplemented by indicators more specific to each degradation process identified or envisaged depending on the environmental conditions of the structure. However, for fire resistance, concrete mixes are prepared using different volume fractions of polypropylene fibers (0.05%, 0.10%, 0.30% and 0.50%), samples are heated to 300 and 600 C, for exposures up to 6 hours, and tested for compressive strength. Based on the results of the study, it is concluded that the relative compressive strengths of concretes containing PP fibers were higher than those of concretes without PP fibers. In addition, it can be concluded that concrete mixes which are prepared using 0.50% PP fibers, by volume, can significantly promote residual compressive strength during heating